A computerized decision support system (CDSS) for antibiotic prescription in primary care—Antibioclic: implementation, adoption and sustainable use in the era of extended antimicrobial resistance. (1st May 2020) - Delory, Tristan; Jeanmougin, Pauline; Lariven, Sylvie; Aubert, Jean-Pierre; Peiffer-Smadja, Nathan; Boëlle, Pierre-Yves; Bouvet, Elisabeth; Lescure, François-Xavier; Le Bel, Josselin
Abstract: Objectives: To describe the implementation and use of a computerized decision support system (CDSS) for antibiotic prescription in primary care in France ( Antibioclic ). The CDSS targets 37 infectious diseases and has been freely available on a website since 2011. Methods: Description and implementation of the architecture of a CDSS for antibiotic prescription in general practice. Analysis of the queries made between 2012 and 2018 on the CDSS by GPs. Analysis of two cross-sectional studies of users in 2014 and 2019. Results: The number of queries increased from a median of 796/day [IQR, 578–989] in 2012 to 11 125/day [5592–12 505] in 2018. Unique users increased from 414/day [245–494] in 2012 to 5365/day [2891–5769] in 2018. Time taken to make a query was 2 min [1.9–2.1]. Among 3 542 347 queries in 2018, 78% were for adults. Six situations accounted for ≥50% of queries: cystitis; acute otitis media; acute sinusitis; community-acquired pneumonia; sore throat; and pyelonephritis. Queries concerned pathologies for which antibiotic prescription was necessary (64%), was conditional on additional clinical steps (34%) or was not recommended (2%). Most users (81%) were GPs, with median age of 38 years [31–52] and 58% were female. Among the 4016 GPs who responded to the surveys, the vast majority (96%) reported using the CDSS during the consultation, with 24% systematically using Antibioclic to initiate an antibiotic course and 93% having followed the CDSS recommendation for the latest prescription. Most GPs were comfortable using the CDSS in front of a patient. Conclusions: Antibioclic has been adopted and is widely used in primary care in France. Its interoperability could allow its adaptation and implementation in other countries.